A group consensus model for evaluating real estate investment alternatives - Wenshuai Wu; Gang Kou (Financial Innovation, 2016)
Background: Individual decision-making largely influences the effectiveness of decisions and benefits of investments. Methods: In this article, a consensus model for group decision-making (GDM), based on the analytic hierarchy process (AHP), is developed to gather group ideas and analyze the real estate investment environment under multi-criteria problems. Twelve evaluation procedures of the developed model, which increase the convergence of the opinions of multiple experts, are proposed. Result: An empirical case about the real estate investment environment is applied to certify the feasibility of this developed model. Conclusions: the evaluation procedures have been fully observed with several rounds of discussions, and have manifested the experiences of experts. Besides, the evaluation results are in accordance with real-world situations, which demonstrates that our developed model is a feasible analysis tool for real estate investors to obtain better profits and lower risk.
Keywords: 650; Group decision-making; Analytic hierarchy process; Real estate investment; Decision analysis